Filogenia, biogeografia, ecologia e evolução de caracteres dos gêneros Melocactus Link & Otto e Discocactus Pfeiff. (Cactaceae) - Telhe, Milena Cardoso (Universidade Federal de São Carlos, 2025)
Despite being well known due to its species richness, a question that has not been deeply discussed is the role of biotic exchanges in maintaining diversity in the Neotropical region. Biota exchange events between distinct habitats have been identified in large numbers in the Neotropical regions, indicating a fundamental role in establishing regional biotas. However, studies involving the role of biotic exchanges on changes in diversification rates are scarce in the Neotropical region, especially between dry and open environments in this region. Although some hypotheses have been proposed to explain the evolutionary consequences of the connection between these environments, few studies have been dedicated to testing them. Thus, more studies are needed to better understand the dispersal and connection between the dry and open biomes of the Neotropical region. The present study aims to investigate the systematic and ecological relationships of Melocactus and Discocactus. Additionally, we investigated biogeographic events within the Melocactus and Discocactus genera, contributing to the understanding of how these events drove diversification in the dry and open biomes of the Neotropical region. For this purpose, the Cactaceae591 probe panel was used to obtain numerous orthologous regions using the sequence capture method. These sequences were used to perform phylogenetic inferences of both genera, estimate diversification ages, infer biogeographic events, and infer the reconstruction of ancestral characters and phylogenetic climatic niches. In addition, diversification rates were estimated to investigate their association with biotic and abiotic variables. In summary, the hundreds of regions sequenced using the Cactaceae591 probe set were able to robustly infer the relationships between and within both genera, allowing taxonomic rearrangements, as demonstrated in chapters 1 and 2. The diversification period of both genera coincides with a period of climate change (Quaternary), alternating between periods of greater aridity and more humid periods. As a consequence of climate change, changes in the distribution of environments also occurred during this period, allowing, for example, the expansion of arid environments during favorable climatic periods, and promoting greater soil heterogeneity throughout the distribution of these environments. The ancestral lineage of both genera originated in a biome composed of Seasonally Dry Forests, later experiencing dispersal events to new areas, such as Savannas. No significant changes in diversification rates were observed in either genus. Biome change events and the presence of adaptive traits are not associated with differences in the diversification rates of the lineages, as demonstrated in Chapter 3. The present study suggests that past climate change and ecological characteristics on a finer scale, such as soil heterogeneity, may have played an important role in the Melocactus and Discocactus diversification.
Phylogeny, biogeography, ecology, and trait evolution of the genera Melocactus Link & Otto and Discocactus Pfeiff. (Cactaceae)
Keywords: Cactaceae591; Especialização edáfica; Trait adaptativo; Mudança de bioma; Filogenômica; Aprendizagem de máquina; Adaphic specialization; Adaptive trait; Biome shift; Phylogenomic; Machine learning; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL